PIV measurements in a real time controlled model wind turbine wake simulator. Issue 3 (September 2016) - Castillo, R; Wang, Y; Monk, T; Vasquez, S; Pol, S; Ren, B; Swift, A; Hussain, F; Westergaard, C H
Abstract: A wind tunnel based "Hyper Accelerated Wind Farm Kinematic-Control Simulator" (HAWKS) is being built at Texas Tech University (TTU) to emulate controlled wind turbine flow physics. The HAWKS model turbine has pitch, yaw and speed controls that could be operated in real time with different power coefficient (Cp) conditions. The purpose of HAWKS is to simulate control strategies, operating at much faster turnaround times. Currently, the fundamental building blocks of the simulator are being tested. A few salient tests results are presented here.